’More Awesome than Electronic Arts’: resistance and appropriation in The Sims gaming communities - Deller, Ruth (AoIR Selected Papers of Internet Research, 2013)
This paper looks at discourses of resistance and appropriation within the gaming communities surrounding The Sims franchise. Fans of this franchise, now in its third iteration (The Sims 3) have long been associated with modding and creating their own custom content for the games (see Gee and Hayes, 2010; Flanagan and Nissenbaum, 2008). Indeed, in the early days of the franchise, the creation of user-generated content was encouraged by the founder of the original game, Will Wright (see Jenkins, 2006). In this paper, I present findings from both a large-scale survey of Sims fans (over 1000 respondents from across a range of communities) and analysis of over forty different Sims blogs, sites and forums to demonstrate how resistance and appropriation form an integral part of the communities’ discourse and activity. through activities such as modding, customisation, user-generated content and piracy and distribution of Electronic Arts content. Much of this activity is framed as being explicitly resistant to Electronic Arts, the company that makes the Sims series. Despite the prevalence of adaptation, appropriation, customisation and resistance practices within the community, some users and bloggers remain vehemently ’anti-modding’, ’anti-piracy’ or both - indeed, they are resistant to these developments. The Sims communities often experience tensions between those who feel they should play the games as designed and those who see gaming as a more user-driven, customisable experience; between those who wish to subvert Electronic Arts and those who do not.